Bionanocomposites based on mesoporous silica and alginate for enhanced drug delivery - de Lima, Hugo H.C.; Kupfer, Vicente L.; Moisés, Murilo P.; Guilherme, Marcos R.; de C. Rinaldi, Jaqueline [UNESP]; Felisbino, Sérgio L. [UNESP]; Rubira, Adley F.; Rinaldi, Andrelson W. (Elsevier, 2018)
This work reports the preparation, the characterization and the prednisolone release profile of biocompatible hydrogel nanocomposites containing mesoporous silica (SBA) and alginate as a biomaterial for enhanced drug delivery with reduced burst effect and improved mechanical properties. Such systems, which were prepared using specific SBA/alginate-crosslinking chemistry, exhibited interconnecting pore hybrid network owing to both mesoporous silica and hydrogel characteristics. Activated SBA was shown to be a determinant factor in inhibiting initial burst by nearly 90% and the drug was released with minimal burst kinetics. The nanoparticles reduced the movements of polymer chains, affecting macromolecular relaxation, and the distribution of mesoporous silica within the hydrogel made drug release into surrounding liquid less favorable. The proposed systems are biocompatible with human immortalized RWPE-1 prostatic epithelial cells. This report offers an approach of up-to-date interest for the development of advanced biomaterials for further physiological and pathological applications.
Keywords: Biomaterials; Cytotoxicity; Drug delivery; Hydrogel; Mesoporous silica; Nanotechnology